Airway luminal area and the resistive work of breathing during exercise in healthy young females and males - Peters, Carli M.; Leahy, Michael G.; Hohert, Geoffrey; Lane, Pierre; Lam, Stephen; Sin, Don D.; McKenzie, Donald C.; Sheel, Andrew William (Journal of applied physiology (1985), 2021)
We hypothesized that the higher resistive work of breathing in females compared with males during high-intensity exercise is due to smaller airways. In vivo measures of the fourth to eighth airway generations made using optical coherence tomography show that females tend to have smaller airway luminal areas of the fourth to sixth airway generations. Sex differences in airway luminal area result in a greater resistive work of breathing during exercise in females compared with males. We examined the relationship between the work of breathing (W b ) during exercise and in vivo measures of airway size in healthy females and males. We hypothesized that sex differences in airway luminal area would explain the larger resistive W b during exercise in females. Healthy participants ( n = 11 females and n = 11 males; 19–30 yr) completed a cycle exercise test to exhaustion where W b was assessed using an esophageal balloon catheter. On a separate day, each participant underwent a bronchoscopy procedure for optical coherence tomography measures of seven airways. In vivo measures of luminal area were made for the fourth to eighth airway generations. A composite index of airway size was calculated as the sum of the luminal area for each generation, and the total area was calculated based on Weibel’s model. We found that index of airway size (males: 37.4 ± 6.3 mm 2 vs. females: 27.5 ± 7.4 mm 2 ) and airway area calculated based on Weibel’s model (males: 2,274 ± 557 mm 2 vs. females: 1,594 ± 389 mm 2 ) were significantly larger in males (both P = 0.003). When minute ventilation was greater than ∼60 L·min −1 , the resistive W b was higher in females. At the highest equivalent flow achieved by all subjects, resistance to inspired flow was larger in females and significantly associated with two measures of airway size in all subjects: index of airway size ( r = 0.524, P = 0.012) and Weibel area ( r = 0.525, P = 0.012). Our findings suggest that innate sex differences in luminal area result in a greater resistive W b during exercise in females compared with males. NEW & NOTEWORTHY We hypothesized that the higher resistive work of breathing in females compared with males during high-intensity exercise is due to smaller airways. In vivo measures of the fourth to eighth airway generations made using optical coherence tomography show that females tend to have smaller airway luminal areas of the fourth to sixth airway generations. Sex differences in airway luminal area result in a greater resistive work of breathing during exercise in females compared with males.